Comparative Study Of Oral Submucosal Fibrosis Management With Two Drug Combination (Triamcinolone And Hyaluronidase) V/S Three Drug Combination (Triamcinolone, Hyaluronidase And Placental Extract) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Oral submucosal fibrosis (OSMF) is a precancerous condition of the oral  mucosa. It is exclusively occurring among Indians and South Asiatic people. It occurs due to  areca nut consumption which leads to inflammation of oral and pharyngeal mucosa and  impaired collagen metabolism. These leads to burning sensation in oral cavity, fibrosis of  mucosal lining and trismus in OSMF. Aim: Aim of the study is to know the effect of triamcinolone, hyaluronidase and placental  extract in different combination in OSMF grade II and III patients. Material& Method: A prospective study of 50 patients was done where they were divided in  two groups. First group was treated with combination triamcinolone & hyaluronidase and  second group was treated with triamcinolone, hyaluronidase and placental extract.  Effectiveness of treatment was measured by visual analogue scale in pre and post treatment  period. Mean score value for each symptoms was compared in two groups. Result: At the end of study, burning sensation showed maximum improvement where mean  score for first group was 0.92±0.15 and 0.84±0.16 in second group. For mouth opening,  mean score of 3.68±0.26 was seen in first group and mean score of 3.24±0.21 was seen in  second group. Both of these results show that second group can give better result compare  to first group. Overall improvement was better in second group on comparing mean value  score. Thus, OSMF patients show significant improvement (
Keywords: Oral submucosal fibrosis; areca nut; triamcinolone; hyaluronidase; placental extract